Psychometric Properties of the Five-Item Francis Attitude Towards Christianity Scale in Colombian Psychiatric Outpatients - Campo-Arias, Adalberto (Journal of religion and health, 2021)
This study aimed to know the psychometric properties of the five-item Francis scale of the attitude towards Christianity (Francis-5) by assessing psychiatric outpatients in Santa Marta, Colombia. A sample of 260 adult patients participated. The exploratory and confirmatory factor analyses revealed an excellent one-dimensional structure with high internal consistency. It was concluded that the Francis-5 exhibited good indicators of validity and reliability in Colombian psychiatric outpatients.